High performance abrasive wear behavior of cemented carbide rods reinforced iron-based composite by synergistic effects of reinforcement and matrix. (12th September 2018) - Yaer, Xinba; Qiqige, Aodun; Wen, Bo; Zhang, Xiujun; Zhang, Mingjian; Cao, Xi; Wang, Jun
Abstract: The study develops a WC-Co rods reinforced based wear resistant composite by the combination of evaporative pattern casting (EPC) process and cast-in insertion method. And then the study investigates the interfacial microstructure between the reinforcement and substrate how to affect the abrasive wear behavior of the composites. It finds that wear resistance of austempered ductile iron (ADI) based composite gets three times of spheroidal graphite cast iron (SGI) not only due to the high performance of ADI, but also the excellent metallurgical bonding. The surface roughnesses of the substrate and the reinforcement in the samples correlate to their contribution rates on wear resistance. The high contribution rates (72.2%) of the substrate and the reinforcement obtained in the ADI based composite allow it possesses the best anti-wear performance. Consequently, the reinforcement protects the substrate from wearing, and the substrate efficiently supports the reinforcement, the stronger these collaborative effects, the more immune to the wear in severe condition.